An Input-Output Analysis of Environmental Effects of Infrastructure Investments in the Greek Economy: The Case of - Attiki Odos - motorway - Athena Belegri-Roboli; Aggeliki Demertzi; Maria Markaki; Panayotis Michaelides (European Regional Science Association (ERSA), 2010)
This paper calculates the environmental effects of the Attiki Odos (AOD) motorway investment expenditures in the Athens Metropolitan Area (AMA), Greece. The AOD is incorporated in the Trans-European Networks (TEN) and is a priority project aimed at developing the AMA. Input - output analysis is applied to assess the environmental impacts of the investments expenditures. More precisely, we apply the environmental input-output life cycle assessment (EIOLCA) method to estimate ex-post the environmental burden associated with the investment vector of AOD. In this context, we calculate each type of emission caused by the AOD investments expenditures (direct, indirect and induced), by sector of economic activity during the construction phase (1999-2004). The investment vector is assembled from figures calculated based on corporate data. Next, in order to estimate the impact of technological change on our estimates, we use ceteris paribus the 2005 input - output table, which expresses, in a nutshell, the production technology of 2005. The domestic input-output tables for 2000 and 2005 come from EUROSTAT. In this framework, the main finding of the paper is that technological change between 2000 and 2005, as expressed through each year's technical coefficients matrix, provided significant results with respect to total output and emissions. Roughly speaking, total output increased approximately by 7% and emissions decreased approximately by 19%.
Keywords: 330